2016
DOI: 10.1155/2016/8905474
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Pattern in the Diagnosis of Gestational Diabetes Mellitus in Southern Sweden

Abstract: Aim. The aim of this study was to examine seasonal patterns in glucose tolerance and in the diagnosis of gestational diabetes mellitus (GDM). Methods. Altogether, 11 538 women underwent a 75-g oral glucose tolerance test (OGTT) in the twenty-eighth week of pregnancy during the years 2003–2005 in southern Sweden. GDM was defined by the 2-h capillary glucose concentration in the OGTT (≥8.9 mmol/L). Chi-squared test, analysis of variance, and regression analyses were used for statistical evaluations. Results. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
49
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(62 citation statements)
references
References 28 publications
7
49
0
Order By: Relevance
“…Our finding that glucose levels in pregnancy varied with ambient temperature is in keeping with a number of previous studies [7,8,10,12,14,15] from various settings around the world. At hotter temperatures, the impact of a fixed glucose load may be greater due to reduced circulating plasma volume, leading to increased diagnoses of GDM.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our finding that glucose levels in pregnancy varied with ambient temperature is in keeping with a number of previous studies [7,8,10,12,14,15] from various settings around the world. At hotter temperatures, the impact of a fixed glucose load may be greater due to reduced circulating plasma volume, leading to increased diagnoses of GDM.…”
Section: Discussionsupporting
confidence: 92%
“…In addition to risk associated with individuals, however, there may also be factors in the general environment that influence the likelihood of GDM. Several recent reports suggest that GDM incidence varies with season in diverse settings including southern Europe [7][8][9], Brazil [10], Australia [11][12][13] and Canada [14,15]. These studies show that postload glucose values and incidence of GDM increase at higher ambient temperatures [7,8,10,13,14].…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…This is despite seasonal trends in GDM previously have been observed in populations in Sweden 13 , Australia 14, 15 , Italy 16 and Greece 17 . However of the populations tested before where no such trend was observed 18,19 one of these was also in the U.K. 19 so our lack of seasonal trend may relate to climate or other environmental factors specific to the U.K. Alternatively, whilst at least one of the studies that found a seasonal trend used a very similar analysis technique to the one that we used 15 , other studies used analysis of variance or categorical/ordinal analyses which did not account for the recurring nature of the seasons or adjust for longer-term temporal trends 13,14,16,17 so differences from our results may relate to this.…”
Section: Discussionmentioning
confidence: 98%
“…9 Therefore another factor that could explain at least part of the increased incidence of GDM is exposure to raised or rising ambient temperatures in certain populations. [10][11][12] Following this some studies have reported seasonal variations in the incidence of GDM [13][14][15][16][17] , although this has not been observed in all populations or climates. 18,19 In this study we investigated whether there were temporal and seasonal trends in GDM incidence in our single centre population from Cambridge, U.K. which recruited pregnant women between 2001 and 2009.…”
Section: Introductionmentioning
confidence: 96%